Anxieties about aging and death and psychological distress: The protective role of emotional complexity. (September 2015) - Bodner, Ehud; Shrira, Amit; Bergman, Yoav S.; Cohen-Fridel, Sara
Highlights: An increase in psychological distress is associated with a rise in aging and death anxieties. High emotional complexity may indicate adaptive emotional regulation among older adults. High emotional complexity protects against the distressful effects of aging and death anxieties. Abstract: Death and aging anxieties are related to higher psychological distress, but no study has examined whether these relationships are moderated by emotional complexity, an important indicator of adaptive emotional regulation among older adults. Participants ( N = 188; mean age = 57; range = 29–100) rated their death and aging anxieties, general psychological distress, and reported their emotions on a daily basis over 14 days. Results showed that emotional complexity moderated the relationship between each of the two anxieties and psychological distress (i.e., the positive relationship between the two anxieties and psychological distress existed only among subjects with low emotional complexity). The findings suggest that emotional complexity buffers against psychological distress, and can be further explored as a facilitating mechanism in protecting against the negative mental health effects of aging and death anxieties.